A systematic review of a digital twin city: A new pattern of urban governance toward smart cities - Deng, Tianhu; Zhang, Keren; Shen, Zuo-Jun (Max) (Journal of management science and engineering (Online), 2021)
Many countries and governments consider smart cities a solution to global warming, population growth, and resource depletion. Numerous challenges arise while creating a smart city. Digital twins, along with the Internet of Things, fifth-generation wireless systems, blockchain, collaborative computing, simulation, and artificial intelligence technologies, offer great potential in the transformation of the current urban governance paradigm toward smart cities. In this paper, the concept of a digital twin city (DTC) is proposed. The characteristics, key technologies, and application scenarios of a DTC are elaborated upon. Further, we discuss the theories, research directions, and framework regarding DTCs.